The Development of Children Pronunciation - Sri Minda Murni; Mutsyuhito Solin (Universitas Medan Area, 2018)
Every child has a unique way of acquiring a language on his way to communicate with people around them. Some children find his way easily to ‘a good and appropriate pronunciation’ while other children ‘create’ his own and unique way. Understanding the pattern of unique or ‘false’ pronunciation can help parents understand their children’s language and be able to respond them appropriately. The study is aimed at describing the pattern of a baby boy’s pronunciation named Ghazi. Ghazi is 2.7 years old. He is mostly taken care by his mom who is a housewife and Dad who likes to spend his time feeding him. Ghazi is a healthy and energetic kid, surrounded by books for children to read and cartoons from youtube to watch. His favorite toy is hot wheels and show a big interest in animals. He has travelled across half of the country, visited many different places, and met different people and relatives to whom he communicates and makes friend easily. Based on his age, Ghazi are in the stage of telegraphic in which children have achieved the competence of SVO structure although still in imperfect grammar which Ghazi has proven to be true for himself. However, Ghazi has his unique ways of pronouncing words which shows particular pattern which is interesting to describe. The study focuses on the pattern of Ghazi’s pronounciation of consonants in the initial and final position and vowels. The results show that: a) Ghazi finds difficulties in pronouncing some consonants in the initial position. The [p] and [b] phonemes become [ʨ] and [d] as in the example [pɔli] becomes [ʨɔyi], [bɔla] becomes [dɔya]; Some phonemes are not spoken at all such as ‘m’ in [mɔbil] which becomes [ɔbin]; b) Ghazi also finds it difficult to pronounce some consonants in the final position. For example, [ɑpel] becomes [ɑpɑn], [panjaŋ] becomes [dɑdɑn], and [mundur] becomes [undun]; c) Ghazi finds some difficulties in pronouncing certain consonants in the initial position but not in the final position. For example, ‘t’ in the initial position is changed such as [təman] becomes [ʨɔman] but ‘t’ in the final position such as [pəsɑwɑt]’ becomes [ʨuʨɑwɑt] which shows no error; d) Ghazi’s difficulties in pronouncing vowels are seen in the example such as [sərɑm],[gəlɑp], and [kərɑs] which become [ʨɔyɑm], [dɔyɑp], and [tɔyɑs] in which that [ə] phoneme becomes [ɔ]. Other vowels do not result in similar difficulties for him. Further researchers are encouraged to find the uniqueness of every child’s pattern of pronunciation to get insight on how children find their own way to a more accepted pronunciation.